The Iconographic Motif of a Griffin and a Hare on the So-called Saracenic-Sicilian Casket from the Wawel Cathedral Treasury in Cracow - Garnczarska, Magdalena (Studia Ceranea, 2015)
The article examines a kind of community of aesthetic tastes that was connecting Arab and Byzantine courtly culture. This community concerned the secular and luxurious works of art. The silver casket, called a Saracenic-Sicilian, from the Wawel Cathedral Treasury in Cracow will serve as the starting point to gain a true appreciation of the complex artistic relationship between the Byzantine Empire and the Islamic world in the Middle Ages. It appears highly probable that the casket was created in the twelfth century. It was published at once after the discovery (8th March 1881) and since then, researchers argue about the place of origin of the box. Some suggest that the casket could be a product of Arabic or Persian art, while others propose either Byzantine or Sicilian workshops. What is more, even an thorough stylistic and iconographic analysis does not allow for an unambiguous resolution of the problem of provenance of the Wawel box. Lack of a resolution suggests that this piece of art was directed to a member of the cosmopolitan elite of – Arabic or Byzantine – court, which took delight in sophisticated and expensive luxury items. It is worth noting that in this case, matter of religion did not play a crucial role. For this reason, the depicted scenes and decorative details have an universal character. In order to present this specific synthesis of Arabic and Byzantine secular art, the motifs of a griffin and a hare, decorating the casket will be considered.